Increased circulating interleukin-8 levels in systemic lupus erythematosus patients: a meta-analysis. (4th December 2018) - Mao, Yan-Mei; Zhao, Chan-Na; Liu, Li-Na; Wu, Qian; Dan, Yi-Lin; Wang, De-Guang; Pan, Hai-Feng
Aim: We performed this meta-analysis in order to evaluate circulating interleukin-8 (IL-8) levels in systemic lupus erythematosus (SLE) patients more accurately and explore its related influencing factors.Methods: The related literature was systematically searched in PubMed, Embase and The Cochrane Library database (up to 28 March 2018). All data analysis was performed by Stata 12.0 software.Results: The results showed SLE patients had a higher circulating IL-8 levels than normal controls (pooled standardized mean difference = 0.963; 95% CI: 0.416–1.511). Subgroup analyses indicated SLE patients with age <40 years, Asia group and disease duration <10 years had higher IL-8 levels.Conclusion: Compared with normal controls, circulating IL-8 levels in SLE patients are elevated and affected by age, region and disease duration. Graphical abstract: